Microwave assisted synthesis of La1−xCaxMnO3 (x = 0, 0.2 and 0.4): Structural and capacitance properties. Issue 17 (1st December 2017) - Tabari, Taymaz; Singh, Dheerendra; Calisan, Atalay; Ebadi, Mehdi; Tavakkoli, Haman; Caglar, Basar
Abstract: The effect of calcium incorporation on the physicochemical and electrochemical properties of the LaMnO3 (LM) perovskites was studied via several techniques. Moreover, a new microwave assisted method was used to synthesize La1−x Cax MnO3 (LCM) perovskites with various calcium content (x = 0.2 and 0.4). Then, the physicochemical properties of the materials such as crystal structure, particle size, surface area, reducibility and band gap energy were investigated by X-ray Diffraction (XRD), High resolution Scanning and Transmission Electron Microscope (HR-SEM and HR-TEM), BET analysis, Temperature-programmed Reduction (TPR) and UV–visible Diffuse Reflectance Spectroscopy (UV–VIS DRS). The increase in partial concentration of calcium resulted in a high specific surface area, larger particle size and an enhanced reducibility along with an increase in the band gap energy. In addition, cyclic voltammetry was applied to LM and LCM perovskites to determine the effect of calcium incorporation on the capacitance of the electrochemical cell. It showed that the capacitance decreases with the amount of Ca 2+ incorporated into the LM structure. This effect is linked to the formation of Mn 4+, which hinders the electron transfer in the structure. The decline in the charge transfer is revealed by the specific capacitance. Finally, our findings showed that the microwave assisted method provides a green, efficient and time-saving route for perovskite synthesis and the calcium incorporation induces a negative effect on the capacitance properties of the LM perovskites.